DAMPAK PANDEMI COVID-19 PADA KOMUNITAS PENGRAJIN PURUN (ELEOCHARIS DULCIS) DI KABUPATEN OGAN KOMERING ILIR, PROVINSI SUMATERA SELATAN, INDONESIA - Ulfa Sevia Azni; Alfitri Alfitri; Yunindyawati Yunindyawati; Riswani Riswani (Jurnal Analisa Sosiologi, 2021)
COVID-19 does not only have an impact on the health side. But it also has an impact on the MSME communities in Indonesia. This study aims to determine the impact of the COVID-19 pandemic on the rural community of Purun craftsmen. This research is qualitative research using the method of observation and in-depth interviews. The findings or results obtained from the impact of COVID-19 on Purun craftsmen caused changes in turnover, decreased orders and income, as well as other obstacles related to business activities such as disrupted production processes and hampered marketing and distribution activities. However, some of the craftsmen affected by the COVID-19 pandemic are still trying to maintain production and others are trying to shift their activities to other types of businesses in order to keep earning income. With the impact of the pandemic being so intensely felt, the community of Purun craftsmen has the opportunity and hope for cooperation from the government and the private sector in establishing an appropriate institutional framework for skills development during the recovery period, assisting the cost and process of making technology infrastructure to facilitate the work of Purun craftsmen, as well as a platform digital for people to promote online sales. Sociologically, the COVID-19 pandemic on Purun craftsmen in rural peatlands can be said to experience the social vulnerability that can cause community social changes, disrupt livelihoods, and community economic resilience. Keywords: Eleocharis dulcis, Purun, Purun crafters, COVID-19. AbstrakCOVID-19 ternyata tidak hanya berdampak pada sisi kesehatan saja. Namun juga berdampak pada komunitas-komunitas UMKM di Indonesia.  Penelitian ini bertujuan untuk mengetahui dampak pandemi COVID-19 pada komunitas pengrajin purun di perdesaan. Penelitian ini merupakan penelitian kualitatif dengan menggunakan metode observasi dan wawancara mendalam. Adapun temuan atau hasil yang diperoleh dari dampak COVID-19 pada pengrajin purun menyebabkan adanya perubahan omset, penurunan order dan pendapatan, serta kendala lain terkait dengan kegiatan usaha seperti proses produksi yang terganggu dan kegiatan pemasaran dan distribusi yang terhambat. Namun sebagian dari pengrajin yang terdampak oleh pandemi COVID-19 ini tetap berusaha untuk mempertahankan produksi dan sebagian lain berusaha untuk mengalihkan kegiatan ke jenis usaha lain agar tetap mendapatkan penghasilan. Dengan dampak pandemi yang begitu sangat dirasakan, komunitas pengrajin purun memiliki peluang serta harapan kerjasama dari pemerintah dan sektor swasta dalam menetapkan kerangka kerja kelembagaan yang sesuai untuk pengembangan keterampilan selama masa pemulihan, membantu biaya dan proses pembuatan infrastruktur teknologi untuk mempermudah pekerjaan pengrajin purun, serta platform digital bagi masyarakat untuk mempromosikan penjualan secara online. Secara sosiologis, pandemi COVID-19 pada pengrajin purun di lahan gambut perdesaan dapat dikatakan mengalami kerentanan sosial yang dapat menyebabkan perubahan sosial komunitas, menganggu mata pencaharian, serta ketahanan ekonomi komunitas. Kata Kunci: Eleocharis dulcis, Pengrajin Purun, COVID-19.